Water‐level dynamics in natural and artificial pools in blanket peatlands. Issue 4 (20th February 2018) - Holden, Joseph; Moody, Catherine S.; Edward Turner, T.; McKenzie, Rebecca; Baird, Andy J.; Billett, Mike F.; Chapman, Pippa J.; Dinsmore, Kerry J.; Grayson, Richard P.; Andersen, Roxane; Gee, Clare; Dooling, Gemma
Abstract: Perennial pools are common natural features of peatlands, and their hydrological functioning and turnover may be important for carbon fluxes, aquatic ecology, and downstream water quality. Peatland restoration methods such as ditch blocking result in many new pools. However, little is known about the hydrological function of either pool type. We monitored six natural and six artificial pools on a Scottish blanket peatland. Pool water levels were more variable in all seasons in artificial pools having greater water level increases and faster recession responses to storms than natural pools. Pools overflowed by a median of 9 and 54 times pool volume per year for natural and artificial pools, respectively, but this varied widely because some large pools had small upslope catchments and vice versa. Mean peat water‐table depths were similar between natural and artificial pool sites but much more variable over time at the artificial pool site, possibly due to a lower bulk specific yield across this site. Pool levels and pool‐level fluctuations were not the same as those of local water tables in the adjacent peat. Pool‐level time series were much smoother, with more damped rainfall or recession responses than those for peat water tables. There were strong hydraulic gradients between the peat and pools, with absolute water tables often being 20–30 cm higher or lower than water levels in pools only 1–4 m away. However, as peat hydraulic conductivity was very low (median of 1.5 × 10 −5 and 1.4 × 10 −6 cm s −1 at 30 and 50 cm depths at the natural pool site), there was little deep subsurface flow interaction. We conclude that (a) for peat restoration projects, a larger total pool surface area is likely to result in smaller flood peaks downstream, at least during summer months, because peatland bulk specific yield will be greater; and (b) surface and near‐surface connectivity during storm events and topographic context, rather than pool size alone, must be taken into account in future peatland pool and stream chemistry studies.